Technique-tactical preparedness of the «Gelios» team (Kharkov) by the results of the 24th Ukrainian football championship in the first league (2014–2015) - Sergey Zhurid; Rebaz Sleman (Слобожанський науково-спортивний вісник, 2015)
Purpose: to define model characteristics of technique-tactical preparedness of the Ukrainian First League football championship with the aim of further improvement and correction of the training process. Material and Methods: the research was conducted using the method of expert evaluation. Results: average meanings of the registered values for 13 games were determined. Different technique-tactical actions and their percentage proportions in the total structure of the team game, statistics for 30 games as well as separate indices of the team play of «Gelios» Kharkov were analyzed. Conclusions: quantitative and qualitative indices (coefficient of defect) both for team technique-tactical actions and separately for each technique-tactical action